Pengaruh Kesehatan, Kecelakaan Dan Keselamatan Kerja Terhadap Motivasi Kerja Di PT Alis Jaya Ciptatama Klaten - Latifah Nur Azizah; Ida Ayu Kade Rachmawati Kusasih (Jurnal Bintang Manajemen, 2023)
The purpose of this study was to determine the effect of Health, Accident and Work Safety on Work Motivation at PT Alis Jaya Ciptatama Klaten. The population in this study were all permanent employees of PT Alis Jaya Ciptatama Klaten. The sample in this study amounted to 75 respondents, the sampling technique used in this study was simple random sampling. The data analysis method used is the Multiple Regression Test which consists of the F test, t test and the coefficient of determination. The results of the simultaneous study (Test F) show that there is a significant influence between Health, Accidents and Work Safety on Work Motivation. Partially (t test) Health and work accidents have no significant effect on work motivation, while work safety has a significant effect on work motivation.